Complex interaction of passive multiport structures and their description by separate discrete models. Issue 1 (1st January 2016) - Ohlrogge, M.; Tessmann, A.; Leuther, A.; Schlechtweg, M.; Ambacher, O.
Abstract : It is demonstrated, using the example of a T‐junction, that not every multiport structure can be accurately described by a discrete and separated modelling approach at millimetre and sub‐millimetre wavelengths. It is shown that especially stub‐networks, which are typically used in RF‐matching networks, are affected. In this case, the discrete modelling approach predicts a different resonance frequency than the S ‐parameter measurement as well as the 3D electromagnetic field simulation (3D‐EMFS) of the whole structure. However, these resonances are of particular importance for the design of a RF matching network and should be predicted by the model as precisely as possible. Therefore, the reason for the mismatch by accurate 3D‐EMFS is investigated and a possible solution on how to model the so‐called complex interactions in passive multiport structures at millimetre and sub‐millimetre wavelengths is provided.